Assessing Health Literacy Among Chinese Speakers in the U.S. with Limited English Proficiency - Chen, Xuewei (Health Lit Res Pract, 2018)
BACKGROUND: Limited English proficiency compounds the problem of low health literacy, making certain population groups in the United States especially vulnerable to health disparities. OBJECTIVE: This study clarified the mechanisms underlying low health literacy among people with limited English proficiency using a modified theory-based health literacy assessment survey. METHODS: We modified and tested the All Aspects of Health Literacy Scale (AAHLS) with a sample of Chinese speakers who have limited English proficiency in the U.S. The AAHLS is a theory-based health literacy survey assessing functional health literacy, interactive health literacy, information appraisal, and empowerment. We adapted the survey, created dual language scenarios (English and Chinese), translated the questions into Chinese, and conducted cognitive interviews to revise the questions. We examined the health literacy score distributions and performed Confirmatory Factor Analysis (CFA) to evaluate the appropriateness of our modified AAHLS to elicit valid data. KEY RESULTS: A total of 405 participants completed our AAHLS survey. Compared to the English language scenario, aside from the item assessing if participants would question health care providers, participants had significantly higher health literacy levels when they were immersed in communication using Chinese (p < .001). We also found that more than three-quarters of the participants were not likely to question their doctor's and nurse's advice regardless of language scenarios and most of them had limited empowerment capabilities at the level of community and social engagement. The CFA results showed that the modified Chinese model exhibited good fit (RMSEA [root mean square error of approximation] = 0.06, CFI [the comparative fit index] = 0.98, TLI [Tucker-Lewis index] = 0.97, WRMR [weighted root mean square residual] = 1). CONCLUSIONS: The results showed that our modified AAHLS yielded reliable and valid data among U.S. Chinese speakers. Researchers should consider native languages and cultural differences before conducting health literacy assessments. Public health professionals should incorporate health interventions and policy approaches to improve Chinese immigrants' English proficiency and empowerment capabilities. [HLRP: Health Literacy Research and Practice. 2018;2(2):e94–e106.] PLAIN LANGUAGE SUMMARY: To clarify the mechanisms underlying low health literacy among populations with limited English proficiency (LEP) in the United States, this study aims to tailor a theory-based health literacy survey with dual-language scenarios among Chinese speakers with LEP. The modified survey yielded reliable and valid data. Participants had higher health literacy levels when they were immersed in communication using Chinese rather than English.